PENGEMBANGAN MODUL SIFAT KOLIGATIF LARUTAN BERBASIS PROBLEM BASED LEARNING UNTUK SISWA SMA/ MA - Marni, Fitria (journal of residu, 2019)
Abstract Colligative Propertise of Solutions is material in chemistry that contain abstract concept, many  students having difficulties in understanding and applying these concepts. So that,  many students having misconception in any material in Colligative Propertise of Solutions. It is easier for students to understand the concept if they are guided to construct their knowledge by finding the concept by themselves  and if they are placed as the subject of study. One of Learning Model that can be used to learn Colligative Propertise of Solutions material that is compatible by its material characteristic is Problem Based Learning Model. This research aims to determine validity and practicallity category from the Module developed. This is Research and Development (R&D) with 4-D Model, that produce a product. 4-D Model consist of four steps: (1) Define (2) Design (3) Develop and (4) Disseminate. The instruments are validity questionnaire and practicallity questionnaire. Data collection technique by spreading the questionnaires and the research result data were analized by Kappa Cohen formula. Analysis result of validity questionnaire shows Moment Kappa Value 0,81 and chategorized very valid. Analysis result of practicallity from teachers are 0,84 (very practice) and students are 0,77 (very practice). Based on the research, Colligative Properties of Solutions Module Based Problem Based Learning for XII class SMA/MA Students  is valid and practice  Keywords: Colligative Propertise of Solution, Problem Based Learning, Module